Kesaksian Non Muslim dalam Putusan Hakim Pengadilan Agama Curup Nomor 571/Pdt. G/2016 - Nashoha, Ahmad; Yusefri, Yusefri; Wihidayati, Sri (Institut Agama Islam Negeri Curup, 2020)
The focus of the study of this article is on the Decision of the Curup Religious Court Judge number 571 / Pdt. G / 2016, which received testimony from non-Muslims. The classical fiqh scholars have formulated that Islam is one of the conditions that must be met in order to receive witnesses or testimony in a trial. As for the non-Muslim witnesses, the fiqh scholars have different opinions. Imam al-Syafi'i flatly rejected it. Other fiqh scholars, from the Hanafiah, Maliki and Hanabilah circles, accept non-Muslim testimonies in certain cases and circumstances. This article examines two issues, first, what the judges consider accepting non-Muslims as witnesses, and second; how is the view from the Maqâshid al-Syarî`ah side. These two problems were analyzed descriptively qualitatively, using the content analysis method and the Maqâshid al-Syarî`ah analysis approach. This article concludes: First, the judge's consideration of receiving non-Muslim testimony in the Curup Religious Court Judge's Decision number 571 / Pdt. G / 2016 is due to the absence of Muslim witnesses. Second, in the perspective of Maqâshid al-Syariah, the acceptance of testimony from non-Muslims in the absence of Muslim witnesses becomes a conditional need so that the case process can be resolved properly and fairly, lâ dharâra wala dhirâr, leading to the maintenance of the benefits of marriage. When Muslim witnesses are not found (absent), the testimony of non-Muslims can be categorized as the benefit of the hajiyat level. namely the level of benefit needed to provide convenience and eliminate difficulties in implementing legal provisions.